Analysis of Cybersecurity EducationPrograms for Undergraduate Students: Review - Kinayat, Gaini; Kurbanali, Nurdaulet; Sadan, Olzhas; Kavkayeva, Nuray; Seisagatova, Anel; Abisheva, Kamilla (Journal of Emerging Technologies and Computing, 2026)
Nowadays, universities are gradually losing the fight against computer-related security concerns, discouraging the development of future professionals in the specialty. Specifically, students are quite knowledgeable when it comes to understanding the notion of information security; however, they lack hands-on experience. The cybersecurity labor shortage has increased by 12.6 percent globally, and employers report that 67 percent of job seekers do not possess sufficient practical skills in the use of security tools and incident response processes. In many cases, there is no structured training, and the fundamentals of security are taught inconsistently. This paper examines the current situation of cybersecurity training in higher education institutions and proposes a model for cybersecurity education. The main objective is to combine theoretical knowledge with practical experience. To achieve this, the study analyzes three established learning platforms, namely TryHackMe, CompTIA, and Fortinet Training Academy, in order to evaluate their pedagogical approaches. Through comparative analysis, a modular program was developed covering the basics of security, network defense, SOC operations, cryptography, DevSecOps, and cloud security. The proposed model incorporates real-life scenarios, practical activities, and case studies, emphasizing experiential learning through simulated environments rather than relying solely on lecture-based instruction. The review reveals several significant gaps in existing curricula, including the absence of practical exercises, lack of coherence in topic sequencing, and non-compliance with industry standards. Although theoretical training on existing platforms is strong, there are limited hands-on labs for vulnerability testing, SIEM training, and incident response. The proposed architecture addresses these gaps by integrating six interrelated domains that reflect real-world cybersecurity processes. It highlights the need to adapt instructional methods to industry-related risks, student learning needs, and employer expectations. The findings indicate that combining theoretical foundations with real-life simulations is essential for preparing students to address real-world cybersecurity challenges. Future work will focus on the practical implementation of the proposed model and pilot testing with undergraduate students for experimental validation.